Cost and effectiveness of omega-3 fatty acid supplementation in Chinese ICU patients receiving parenteral nutrition - Wu, Guo Hao (Clinicoecon Outcomes Res, 2015)
BACKGROUND AND OBJECTIVES: Clinical evidence supports the use of omega-3 polyunsaturated fatty acid (PUFA)-enriched lipid emulsions in place of standard lipid emulsions in parenteral nutrition (PN) for intensive care unit (ICU) patients, but uptake may be limited by higher costs. We compared clinical and economic outcomes for these two types of lipid emulsion in the Chinese ICU setting. METHODS: We developed a pharmacoeconomic discrete event simulation model, based on efficacy data from an international meta-analysis and patient characteristics, resource consumption, and unit costs from a Chinese institutional setting. Probabilistic sensitivity analyses were undertaken to assess the effects of uncertainty around input parameters. Model predictive validity was assessed by comparing results with data observed in a patient subset not used in the modeling. RESULTS: The model predicted that omega-3 PUFA-enriched emulsion (Omegaven(®) 10% fish oil emulsion) would dominate standard lipid emulsions, with better clinical outcomes and lower overall health care costs (mean savings ~10,000 RMB), mainly as a result of faster recovery and shorter hospital stay (by ~6.5 days). The external validation process confirmed the reliability of the model predictions. CONCLUSION: Omega-3 PUFA-enriched lipid emulsions improved clinical outcome and decreased overall costs in Chinese ICU patients requiring PN.